The effectiveness of transnasal high flow nasal cannula in bronchoscopy under sedation: a systematic review and meta-analysis - Wei, Chen; Ma, Shaoyong; Wang, Jingwen; Yang, Na; Wang, Dandan; Yuan, Liping; Wang, Yingying (Frontiers in Medicine, 2024)
Background:: The objective of this study was to conduct a systematic review and meta-analysis of the clinical application effects of transnasal high flow nasal cannula compared to other conventional modalities for oxygen therapy devices in patients undergoing bronchoscopy.Methods: A comprehensive literature search was conducted in multiple English databases, including PubMed, Web of Science, and Cochrane Library, to collect relevant studies on the application of high flow nasal cannula in patients undergoing bronchoscopy ， and conducted a meta-analysis utilizing RevMan 5.4 software, following the predetermined inclusion and exclusion criteria.Results: A total of 12 studies meeting the inclusion criteria were included, involving 1631 patients (HFNC group: n = 811, other oxygen therapy group: n = 820). The meta-analysis results demonstrated that HFNC significantly reduced the incidence of hypoxemia and improved the minimum oxygen saturation compared to conventional oxygen therapy (RR = 0.27, 95% CI: 0.18-0.41, P < 0.00001; MD = 6.09, 95% CI: 3.73-8.45, P < 0.00001). Furthermore, HFNC showed statistically significant differences when compared to non-invasive ventilation in terms of hypoxemia incidence (RR = 3.52, 95% CI: 1.13-10.97, P = 0.03) and minimum oxygen saturation (MD = -1.97, 95%